Patient profile based management approach for Optimal Treatment of Angina: a consensus from India cases - Shah, V. T.; Zachariah, Geevar; Lakshmanan, S.; Babu, Surendra; Suresh, K.; Ghosh Roy, Devanu; Shah, Bhupesh; Baxi, Hemang; Tripathi, M. P.; Saran, R.; Kuruttukulam, Sajy; Vaidhyanathan, P. R.; et al. (International Journal of Advances in Medicine, 2019)
Chronic stable angina (CSA) is an incapacitating disorder. The pain can hinder the routine chores of an individual and significantly impact one’s quality of life (QoL). However, the good news is that this can be treated and the QoL can be improved. The key to apt management lies in the accurate early diagnosis of this condition, followed by a detailed evaluation and accordingly planned management, which should be regularly revised and be backed by an adequate follow-up. OPTA-OPtimal Treatment for chronic stable Angina-is an educational initiative to assist the clinicians in India with screening and diagnostic tools, strengthened by updated guideline-directed management to ensure satisfactory patient outcomes. OPTA aims to improve clinical outcomes by providing optimized pharmacotherapy for patients with stable angina. This expert consensus document intends to provide information for better understanding of the condition by clinicians and to ensure an early, accurate diagnosis, followed by optimal management of angina. For better clinical and practical understanding of Indian clinical scenario, the most commonly encountered patient profiles are briefly described here. These inputs and an extensive literature review were blended to develop the recommendations for clinicians across the country. An attempt is made to include clinical recommendations that meet the needs of the majority of patients in most circumstances in the Indian scenario. However, the ultimate judgment regarding individual case management should be based on clinician’s discretion. This expert consensus document is not a substitute for textbooks and/or a clinical judgment.